2020
DOI: 10.4103/jfmpc.jfmpc_1352_20
|View full text |Cite
|
Sign up to set email alerts
|

Profile, risk factors and outcome of occupational injuries reported to the emergency department in a tertiary care hospital in South India

Abstract: Background: India is an industrialised country and most work is labour intensive. There is very scarce data on occupation related injuries Aim: To evaluate the prevalence, profile, severity and risk factors for occupational injuries presenting to the emergency medicine department of a tertiary care hospital. Materials and Methods: A cross-sectional study was done in the emergency department of Christian Medical College, Vellore among the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Those patients with history of occupational eye accident before, had higher risk of occupational eye injuries (AOR: 8.4) (Table 2) , and this agreed with that detected in Italy where the workers with previous occupational eye injury were at potential risk for new eye injuries (Gobba et al, 2017). Similarly, a study in India found that the workers proneness to occupational injuries increased with previous ones (Regina et al, 2020) .…”
Section: Discussionsupporting
confidence: 82%
“…Those patients with history of occupational eye accident before, had higher risk of occupational eye injuries (AOR: 8.4) (Table 2) , and this agreed with that detected in Italy where the workers with previous occupational eye injury were at potential risk for new eye injuries (Gobba et al, 2017). Similarly, a study in India found that the workers proneness to occupational injuries increased with previous ones (Regina et al, 2020) .…”
Section: Discussionsupporting
confidence: 82%
“…[ 8 ] Similarly, mostly (86%) males suffered from occupational accidents in South India. [ 5 ] The majority of the victims (73.10–97.50%) injured due to occupational accidents in Turkey were male. [ 10 – 15 ] This was related to the fact that men were more involved in work and worked more in heavy jobs.…”
Section: Discussionmentioning
confidence: 99%
“…In Southern India, the abdomen and pelvis were the most frequently injured body parts in traumatic work accidents (36%). [ 5 ] In Northern Italy, the predominant area of injury in fatal occupational accidents was the head (33.56%). [ 1 ] Upper extremity injury (50%) was seen at a higher rate than other body parts in Glasgow, England.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations